2019
DOI: 10.4081/aiua.2019.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Transumbilical laparoendoscopic single-site adrenalectomy: A feasible and safe alternative to standard laparoscopy

Abstract: Objectives: Standard multi-port laparoscopic adrenalectomy (LA) is considered the gold standard for benign adrenal tumors. Single-site LA has been proposed as a feasible and safe alternative because of lower invasiveness, improved cosmetics, less pain and shorter hospital stay. The objective was to evaluate and compare results of single-site transumbilical laparoendoscopic adrenalectomy with standard LA for adrenal tumors. Materials and methods: One hundred consecutive adrenalectomies from 93 patients, perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The sample size of the studies ranged from 22 to 210 patients. A commercially available multichannel port device was used for LESS-A in the majority of the studies [ [13] , [14] , [15] , [19] , [20] , [21] , [24] , [25] , [26] , 28 , 30 , 31 , 33 , 41 ]. Three studies used a single glove or a commercially available multichannel port device [ 22 , 32 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample size of the studies ranged from 22 to 210 patients. A commercially available multichannel port device was used for LESS-A in the majority of the studies [ [13] , [14] , [15] , [19] , [20] , [21] , [24] , [25] , [26] , 28 , 30 , 31 , 33 , 41 ]. Three studies used a single glove or a commercially available multichannel port device [ 22 , 32 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results revealed no significant difference in postoperative pain scores between LESS-A and m-LA in the subset analysis. Five studies reported the use of postoperative pain medication [ 13 , 15 , 19 , 30 , 33 ]. Postoperative pain medication was administered to 48.03% patients (73/152 patients) treated with LESS-A, and the percentage was 69.27% (133/192 patients) for those treated with m-LA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional open surgery has disadvantages, such as the creation of a large incision, difficulty achieving deep exposure, severe trauma, and a long recovery period. Since the first report of laparoscopic adrenalectomy[20], laparoscopic adrena-lectomy has been frequently reported[21-23]. The application of laparoscopy in NB resection is very extensively reported in the literature; however, if the NB is closely associated with important blood vessels, the use of a laparoscope in NB resection is still challenging and has limitations.…”
Section: Discussionmentioning
confidence: 99%